Samba virus: a novel mimivirus from a giant rain forest, the Brazilian Amazon - Campos, Rafael K (BioMed Central, 2014)
BACKGROUND: The identification of novel giant viruses from the nucleocytoplasmic large DNA viruses group and their virophages has increased in the last decade and has helped to shed light on viral evolution. This study describe the discovery, isolation and characterization of Samba virus (SMBV), a novel giant virus belonging to the Mimivirus genus, which was isolated from the Negro River in the Brazilian Amazon. We also report the isolation of an SMBV-associated virophage named Rio Negro (RNV), which is the first Mimivirus virophage to be isolated in the Americas. METHODS/RESULTS: Based on a phylogenetic analysis, SMBV belongs to group A of the putative Megavirales order, possibly a new virus related to Acanthamoeba polyphaga mimivirus (APMV). SMBV is the largest virus isolated in Brazil, with an average particle diameter about 574 nm. The SMBV genome contains 938 ORFs, of which nine are ORFans. The 1,213.6 kb SMBV genome is one of the largest genome of any group A Mimivirus described to date. Electron microscopy showed RNV particle accumulation near SMBV and APMV factories resulting in the production of defective SMBV and APMV particles and decreasing the infectivity of these two viruses by several logs. CONCLUSION: This discovery expands our knowledge of Mimiviridae evolution and ecology.